Quality of therapy in early ovarian cancer: results of the quality assurance program of the AGO Study Group - Wimberger, Pauline; Pfisterer, Jacobus; Du Bois, Andreas; Hilpert, Felix; Kerkmann, Markus; Sehouli, Jalid; Mahner, Sven; De Gregorio, Nikolaus; Hanker, Lars; Heitz, Florian; Marmé, Frederik; Wölber, Linn; et al. (International journal of gynecological cancer, 2023)
Objective The quality assurance program for ovarian cancer (QS-OVAR) evaluates the implementation of treatment standards and impact on survival for International Federation of Gynecology and Obstetrics (FIGO) stage I ovarian cancer. - Methods Patients with a first diagnosis of ovarian cancer, diagnosed in the third quarter of 2004, 2008, 2012, and 2016, were documented. Surgical quality was categorized as optimal (maximum one surgical item missing) versus suboptimal (≥2 surgical items missing). Chemotherapy was defined as optimal according to national guidelines. Treatment quality was classified into four categories: surgery and chemotherapy were optimal, optimal surgery and suboptimal chemotherapy, suboptimal surgery and optimal chemotherapy, and surgery and chemotherapy were suboptimal. - Results In total, 19.9% (n=700) of ovarian cancer patients were diagnosed with FIGO stage I. Median age was 60 years (range 18-96), 47.1% had FIGO stage IA and 47.9% had stage IC, with 37.1% high grade serous histology. Optimal surgical quality increased over time from 19.9% to 54.1%. The optimal surgery population increased from 42.2% to 70.9%. Disease free survival improved significantly in the optimal surgery population (84% after 48 months vs 71% in the suboptimal surgery population). Overall survival increased with 91% after 48 months in the optimal surgery population versus 76% in the suboptimal surgery population. In total, 20.7% of patients were undertreated concerning systemic treatment and 1% overtreated. Optimal chemotherapy standard was administered increasingly over time (71.4-80.8%). Disease free survival and overall survival were prolonged with adjuvant chemotherapy. The optimal surgery/chemotherapy subgroup increased from 37.9% to 54.1% with significantly longer disease free survival and overall survival (overall survival at 48 months: optimal surgery and chemotherapy 93%; suboptimal surgery and chemotherapy 68%). - Conclusion Although QS-OVAR data showed that the quality of therapy has improved over the years, not all surgical standards were met in nearly 50% of patients. The steady increase in the optimal surgery and chemotherapy collective is an important tool for improvement of prognosis of ovarian cancer patients.
Online veröffentlicht: 31. März 2023
Gesehen am 16.07.2024